(Un)Conditional Welfare? Tensions Between Welfare Rights and Migration Control in Swiss Case Law - Borrelli Lisa Marie; Kurt Stefanie; Achermann Christin; Pfirter Luca (Swiss Journal of Sociology)
This analysis of Swiss Federal Supreme Court judgements shows the coupling of welfare and migration control. Foreign nationals depending on social assistance might face the withdrawal of their residence permits. We show how the conveyed legal logics create conditionality of rights and a differentiation of (non-)citizens. The judgements individualise social assistance dependence and follow a neoliberal logic of economic participation. They establish rationalities which reinforce politics of belonging and welfare chauvinism.